A course design to develop meta-cognitive skills for collaborative knowledge building through tool-assisted discourse analysis. (1st January 2014) - Matsuzawa, Yoshiaki; Tohyama, Sayaka; Sakai, Sanshiro
This paper presents the design of a course called 'learning management'. The proposed course is intended for first-year undergraduate students and has the goal of helping students to 'learn collaborative learning'. The class design is intended to help in transforming student beliefs about learning by replacing the passive, individual model of learning with an active, collaborative model that is supported by the concept of knowledge building. We conducted an empirical study in which students analysed their own discourse. Students in the experimental group used the KBDeX software to assist their analysis, and students in the control group reflected on their project activities in whatever way they chose. We used qualitative analysis of post-project reports to examine the change in student beliefs. The results showed that the course design encouraged transformation of beliefs about learning, with students moving from viewing the course as just participating in collaborative learning to viewing it as actively contributing to collaborative knowledge creation. This result also shows that we succeeded in changing the students' perceptions about collaborative learning from negative to positive.